Caregiver perspectives on the long-lasting impact of the COVID-19 pandemic on children with cerebral palsy in Johannesburg, South Africa - Skye Nandi Adams; Razina Bhorat; Aneesah Moosa (BMJ Paediatrics Open)
Background The COVID-19 pandemic exacerbated challenges faced by children with cerebral palsy (CP), including limited access to therapy services, financial strain and disruptions in schooling and social activities. However, the specific long-lasting impacts of the pandemic on families of children with CP in the South African context remain underexplored.Aim To explore the long-lasting impact of the COVID-19 pandemic on children with CP in South Africa.Method A qualitative exploratory approach was used. 14 caregivers of 12 children with CP (aged 4–12) were recruited from various CP-specific schools and organisations in urban Johannesburg, South Africa. Individual semistructured interviews were conducted, and each interview was audio recorded, transcribed verbatim and analysed using inductive thematic analysis.Results Children experienced significant changes to their physical and emotional well-being during the pandemic that had long-lasting effects on their added weight gain and activities of daily living. Many children experienced regressions during the lockdown due to the closure of schools and therapy centres. However, increased screen time observed among children with CP during the pandemic yielded unexpected positive outcomes, such as the improvement of technological skills and enhanced confidence through activities like vlogging.Implications The pandemic has had long-lasting impacts on children with CP and addressing the multifaceted challenges faced by children with CP and their families in the post-COVID-19 era requires coordinated efforts from all stakeholders to ensure the holistic well-being and inclusion of this vulnerable population. Further research is warranted to assess the long-term impacts of the pandemic and evaluate the effectiveness of interventions aimed at mitigating its effects on this vulnerable population.